ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Irawan, Ade; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2013)
The purpose of this study was to analyze the effect of the variable firm size (Size), business risk (risk), and liquidity (CR) of the debt policy (DTA) and the effect of the debt policy on firm value (PBV) in the companies listed on the Indonesia Stock Exchange (BEI) the period of 2007-2011. This study uses purposive sampling method to take samples. The data obtained based on the publication of Indonesian Stock Exchange (IDX), obtained a total sample of 32 companies. The analysis technique used is multiple regression analysis stages. Hypothesis testing using the t test. Similarly, the business risk variable positive and significant effect on the debt policy because it has a significance value smaller than 5% level. While the liquidity variable and significant negative effect on the debt policy because it has significant value which is lower than the 5% significance level. And the debt policy itself has a positive and significant impact on firm value.